Assessing social innovation in real time - Molina, Alfonso; Michilli, Mirta (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Real-Time Evaluation for Social Innovation (RTE4SI) is a dynamic, adaptive, and narrative method that integrates monitoring and evaluation to continuously collect and use data. It constantly updates, includes immediate responses to results, and translates data into stories of impact. By mapping connections between resources, activities and changes, it supports the analysis of short-, medium- and long-term transformations, verifying the success of innovation.